Preparation method of porous filter

The new ceramic porous filter prepared by adhesive jet 3D printing technology solves the slag dropping and damage caused by the fragility of traditional filters, and achieves higher casting quality and yield.

CN119795323AActive Publication Date: 2025-04-11JINAN SHENGQUAN GRP SHARE HLDG CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411996455.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The internal structure of existing foam ceramic filters is fragile and prone to slag and damage during transportation and casting, resulting in a decrease in casting quality.

Method used

New ceramic porous filters are prepared by adhesive jet 3D printing technology, and the strength and high temperature resistance of the filter are improved by selecting appropriate printing materials and processes.

Benefits of technology

The prepared new ceramic filter has a strong skeleton structure and good high temperature resistance, which avoids slag dropping and damage problems, and improves the yield and quality of castings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005224689330000171
    Figure BDA0005224689330000171
  • Figure BDA0005224689330000181
    Figure BDA0005224689330000181
  • Figure BDA0005224689330000182
    Figure BDA0005224689330000182
Patent Text Reader

Abstract

The invention provides a preparation method of a porous filter, which comprises the following steps: granulating and preparing a granular material; mixing the granules and a curing agent to form a printing raw material; a printing raw material is flatly laid, a binder is sprayed to a preset position, and the processes of flatly laying and spraying the binder are repeated to obtain a green body; and sintering the green body to form the porous filter. The filter prepared by the preparation method provided by the invention has relatively high strength in a blank body stage and after sintering, and when the filter is used for casting, the filter has high strength and high thermal stability, and compared with the prior art, the filter also has quicker casting time and higher casting quantity. Therefore, the possibility that the interior of the filter is thin, fragile, slag-falling and damaged is reduced, and the working requirements of daily transportation and high-temperature filtration can be well met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This technology belongs to the field of additive manufacturing, and specifically relates to a molding technology and method for a new type of ceramic porous high-temperature resistant material. Background Art

[0002] 3D printing, also known as additive manufacturing, is a rapid prototyping manufacturing method. 3D printing includes a variety of molding processes according to different molding methods. Among them, binder jet 3D printing technology (also known as 3DP or BJ printing) is a molding process that combines precision and efficiency. This process is based on the principle of using a piezoelectric nozzle to spray adhesive to bond powder particles into shape. At present, the molding accuracy of 3DP printing equipment can reach ±0.3mm, which meets the mold's precision requirements. In recent years, binder jet 3D printing technology has developed rapidly in China and has become one of the most vital rapid printing and molding technologies.

[0003] Molten liquid metal often contains different oxides and impurities, which will affect the metal crystal form, and the mechanical properties of the metal after forming will be greatly reduced, which is something that is not desirable in the casting field. At present, foam ceramic filters and straight hole pressed filters are mainly used to achieve the purpose of filtering, so as to remove impurities in the molten metal and achieve the purpose of rectification and adsorption, and these foam ceramic filters are divided into silicon carbide filters and zirconium oxide filters according to their high temperature resistance. At present, the preparation method of foam ceramic filters is mainly based on the structure of polyurethane foam, and high temperature resistant slurry is coated on the foam to make it evenly coated on the surface of polyurethane foam, and then the organic part is sintered in a high temperature furnace, and the remaining foam ceramic body with different high temperature resistance is achieved to achieve the purpose of preparing foam ceramic filters. However, some parts of the internal structure of the current foam ceramic filter are relatively slender and fragile, and there is a possibility of slag and damage when transporting and casting molten metal liquid, and the slag or defective parts have an immeasurable impact on the casting. Summary of the invention

[0004] In order to solve the problem that filters in the prior art have many defects and are prone to falling off during the filtering of molten iron, the present application adopts binder jet 3D printing technology to prepare a new type of ceramic porous high-temperature resistant filter. The filter has a strong and complete skeleton structure, good high-temperature resistance during the filtering of molten metal, will not cause defects and slag falling problems, and improves the yield and quality of castings.

[0005] The specific technical solutions of this application are as follows:

[0006] 1. A method for preparing a porous filter, wherein the method comprises:

[0007] Granulation: fine refractory particles, binder, solvent and additives are mixed in a mass ratio of (90-100): (1-5): (5-15): (0.5-10), and then granulated to prepare granular materials;

[0008] Printing materials: Mix the granular material and the curing agent to form printing materials;

[0009] A three-dimensional model of the blank to be printed is established, and then the three-dimensional model is input into a computer to obtain the number of layers of printing material required for the blank to be printed and the corresponding bonding areas between the layers, that is, the preset positions for the injection of the binder.

[0010] The printing material is laid flat, and a binder is sprayed at a preset position, and the laying flat and the binder spraying processes are repeated to obtain a blank.

[0011] The green body is sintered to form a porous filter.

[0012] 2. The method according to item 1, wherein the fine refractory particles are selected from one or more of mullite, silicon carbide, silicon dioxide, alumina, and zirconium oxide; preferably silicon dioxide and alumina, and more preferably, the ratio of silicon dioxide to alumina is 1:(0.6-1.5) by mass; and / or

[0013] The adhesive is selected from one or more of furan resin, phenolic resin, urea-formaldehyde resin adhesive, polyvinyl acetal adhesive, polyvinyl acetate (PVAc) emulsion, acrylic acid ester water-based adhesive, rubber emulsion adhesive, polyurethane water-based adhesive, cement, gypsum, water glass, lime, and clay; and / or

[0014] The solvent is selected from one or more of water, methanol, ethanol, ethylene glycol, acetone, chloroform, carbon tetrachloride, ether, gasoline, benzene, toluene and xylene; the solvent is preferably water or methanol; and / or

[0015] The additive is selected from one or more of sulfates, sulfonates, phosphates, amine salts, and polyethylene glycol.

[0016] 3. The method according to item 2, wherein the ratio of the fine refractory particles to the binder is 100:(1 to 3) by mass; and / or

[0017] The sphericity of the granules is 0.95-1.

[0018] 4. The method according to claim 1, wherein the particle size distribution of the granular material is 40-245 microns.

[0019] 5. The method according to item 1, wherein, in the process of forming the printing raw material, the mass ratio of the curing agent to the particulate material is (0.20-0.65):100.

[0020] 6. The method according to item 5, wherein the curing agent is selected from one or more of sulfate, p-toluenesulfonic acid, xylenesulfonic acid, benzenesulfonic acid, sulfuric acid, phosphoric acid, mixed xylenesulfonic acid, lactic acid, citric acid, maleic anhydride, and oxalic acid.

[0021] 7. The method according to item 1, wherein a sintering aid is added to the printing material before tiling, and the mass ratio of the printing material to the sintering aid is 100:(1.8-23).

[0022] 8. The method according to item 7, wherein the sintering aid is selected from one or more of amorphous silica, carbide, boride, oxide, spherical calcium aluminate, and aluminum fluoride granules, preferably amorphous silica, spherical calcium aluminate, and aluminum fluoride granules are used in combination.

[0023] 9. The preparation method according to item 8, wherein the D50 particle size of the amorphous silica is 0.5-3 μm.

[0024] 10. The method according to item 1, wherein the binder is selected from one or more of polyvinyl alcohol (PVA), polyvinyl ketone (PVP), polyacrylic acid (PAA), furan resin, phenolic resin, epoxy resin, urea-formaldehyde resin adhesive, polyvinyl acetal adhesive, polyvinyl acetate (PVAc) emulsion, acrylate water-based adhesive, polyurethane water-based adhesive, water glass, phosphate, and polyurethane acrylate, and the binder is preferably furan resin.

[0025] 11. The method according to item 1, wherein the tensile strength of the blank is 2.0-5.0 MPa.

[0026] 12. The method according to item 1, wherein before sintering the green body, a post-processing step is further included, wherein the post-processing step comprises the following steps:

[0027] The green body is immersed in a fine powder solution to increase the volume density of the green body.

[0028] 13. The method according to item 1, wherein, during the sintering process, the green body is sintered for the first time at a temperature of T1, and after the first sintering, is sintered for the second time at a temperature of T2, thereby obtaining the porous filter.

[0029] 14. The method according to item 13, wherein, during the first sintering process, the T1 temperature is 800-900°C, the sintering time is 2h-4h; the pressure during the sintering process is normal pressure; and / or

[0030] During the second sintering process, the T2 temperature is 1200-1750° C., the sintering time is 4h-6h; and the pressure during the sintering process is normal pressure.

[0031] 15. The method according to any one of items 1 to 14, wherein the compressive pressure of the porous filter at temperature T3 is 1.3-2.5 MPa, and the compressive pressure at temperature T4 is 0.6-1.5 MPa;

[0032] Wherein, the temperature range of T3 is 10-30°C, and the temperature range of T4 is 900-1200°C.

[0033] 16. A porous filter, wherein the porous filter is prepared using the method described in any one of items 1 to 15.

[0034] Effects of the Invention

[0035] This application uses binder jet 3D printing technology to prepare a new type of ceramic porous high-temperature resistant filter. Through the selection, synthesis and proportion of printing materials, and the soaking and densification of the printed blank, the prepared filter has higher stress strength and compressive resistance.

[0036] The novel ceramic filter prepared by the preparation method of the present application has high strength at both room and high temperatures, which solves the problem of easy slagging and uneven coarseness of traditional foam filters, and ensures that the molten iron is not contaminated by slagging materials during the casting process.

[0037] The internal flow channel of the new ceramic filter prepared by the preparation method of the present application can be modeled and designed to have an internal structure suitable for high-temperature molten iron fluid, which can not only ensure the flow rate of the molten iron in its channel, but also effectively filter out the impurity content in the molten iron, thereby ensuring the casting quality. DETAILED DESCRIPTION

[0038] The embodiments described below are described in detail for the present application. Although specific embodiments of the present application are shown, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present application and to fully convey the scope of the present application to those skilled in the art.

[0039] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the functional differences of components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" are open-ended terms and should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the present application, but the description is based on the general principles of the specification and is not intended to limit the scope of the present application. The scope of protection of the present application shall be determined by the attached claims.

[0040] The following embodiments of the present application are only used to illustrate the specific embodiments of the present application, and these embodiments cannot be understood as limiting the present application. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present application are deemed to be equivalent replacement methods and fall within the scope of protection of the present application.

[0041] The specific embodiments of the present application will be described in more detail below. However, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present application and to enable the scope of the present application to be fully communicated to those skilled in the art.

[0042] As used in this specification, "a" or "an" may mean one or more. As used in the claims, when used with the word "comprising", the word "a" or "an" may mean one or more than one.

[0043] The term "or" is used in the claims to mean "and / or" unless explicitly stated to refer only to alternatives or the alternatives are mutually exclusive, although the present disclosure supports a definition referring only to alternatives and "and / or." As used herein, "another" may mean at least a second or more.

[0044] The present application relates to a method for preparing a porous filter, wherein the method comprises:

[0045] Granulation, mixing fine refractory particles, a binder, a solvent and an additive in a mass ratio of (90-100): (1-5): (5-10): (0.5-10), and then granulating to prepare a granular material;

[0046] Printing materials: Mix the granular material and the curing agent to form printing materials;

[0047] Specifically, the printing material is first spread out in a layer on the material box, and a binder is sprayed at a preset position. At this time, a layer of jet printing is completed. After the jet printing is completed, the material box is lowered by one layer, and the process of spreading and spraying the binder is repeated to obtain a blank; the blank is sintered to form a porous filter.

[0048] In one embodiment of the present application, during the granulation process, the ratio of the fine refractory particles to the binder may be 100:(1-3) by mass.

[0049] In one embodiment of the present application, during the granulation process, the ratio of the fine refractory particles to the binder may be 100:(1-5) by mass.

[0050] Specifically, in the granulation process, the ratio of the fine refractory particles to the binder can be 90:1, 90:2, 90:3, 90:4, 90:5, 91:1, 91:2, 91:3, 91:4, 91:5, 92:1, 92:2, 92:3, 92:4, 92:5, 93:1, 93:2, 93:3, 93:4, 93:5, 94:1, 94:2, 94:3, 94:4, 94:5. 4:5, 95:1, 95:2, 95:3, 95:4, 95:5, 96:1, 96:2, 96:3, 96:4, 96:5, 97:1, 97:2, 97:3, 97:4, 97:5, 98:1, 98:2, 98:3, 98:4, 98:5, 99:1, 99:2, 99:3, 99:4, 99:5, 100:1, 100:2, 100:3, 100:4, 100:5.

[0051] In one embodiment of the present application, during the granulation process, the ratio of the fine refractory particles to the solvent may be 90:5, 90:10, 90:15, 91:5, 91:10, 91:15, 92:5, 92:10, 92:15, 93:5, 93:10, 93:15, 94:5, 94:10, 94:15, 95:5, 95:10, 95:15, 96:5, 96:10, 96:15, 97:5, 97:10, 97:15, 98:5, 98:10, 98:15, 99:5, 99:10, 99:15, 100:5, 100:10, 100:15.

[0052] In one embodiment of the present application, during the granulation process, the ratio of the fine refractory particles to the additive may be 90:0.5, 90:1, 90:5, 90:10, 91:0.5, 91:1, 91:5, 91:10, 92:0.5, 92:1, 92:5, 92:10, 93:0.5, 93:1, 93:5, 93:10, 94:0.5, 94:1, 94:5, 94:10. 4:5, 94:10, 95:0.5, 95:1, 95:5, 95:10, 96:0.5, 96:1, 96:5, 96:10, 97:0.5, 97:1, 97:5, 97:10, 98:0.5, 98:1, 98:5, 98:10, 99:0.5, 99:1, 99:5, 99:10, 100:0.5, 100:1, 100:5, 100:10.

[0053] In one embodiment of the present application, the fine refractory particles are selected from one or more of mullite, silicon carbide, silicon dioxide, alumina, and zirconium oxide; the fine refractory particles are preferably silicon dioxide and alumina. The ratio of silicon dioxide to alumina is 1:(0.6-1.5) by mass, for example, 1:0.6, 1:0.65, 1:0.7, 1:0.75, 1:0.8, 1:0.85, 1:0.9, 1:0.95, 1:1.0, 1:1.05, 1:1.1, 1:1.15, 1:1.2, 1:1.25, 1:1.3, 1:1.35, 1:1.4, 1:1.45, 1:1.5.

[0054] The adhesive is selected from one or more of furan resin, phenolic resin, urea-formaldehyde resin adhesive, polyvinyl acetal adhesive, polyvinyl acetate (PVAc) emulsion, acrylate water-based adhesive, rubber emulsion adhesive, polyurethane water-based adhesive, cement, gypsum, water glass, lime, and clay; the adhesive is preferably phenolic resin.

[0055] The solvent is selected from one or more of water, methanol, ethanol, ethylene glycol, acetone, chloroform, carbon tetrachloride, ether, gasoline, benzene, toluene and xylene; the solvent is preferably water or methanol.

[0056] The additive is selected from one or more of sulfates, sulfonates, phosphates, amine salts, and polyethylene glycol, and the additive is preferably polyethylene glycol.

[0057] It should be understood that any one of the fine refractory particles, binder, solvent and additives can be composed of multiple substances in any proportion. For example, the fine refractory particles can be selected from two or more substances mixed in any proportion, or only one substance can be used.

[0058] For example, the solvent may be selected from two or more solvents that are miscible in any proportion, or only one solvent may be used. In one embodiment of the present application, the solvent is all water. In one embodiment of the present application, the solvent is only alcohols. In one embodiment of the present application, the solvent is a mixture of ethanol and methanol, and in one embodiment of the present application, the mass ratio of ethanol to methanol in the solvent is 1:9.

[0059] In the present application, the granulation can be carried out using any granulation method well known to those skilled in the art, such as wet granulation, one-step granulation, spray granulation, dry granulation, etc., and there is no limitation in the present application.

[0060] In the present application, "sphericity" refers to a parameter that characterizes the morphology of particles. The closer the particles are to a sphere in morphology, the closer their sphericity is to 1. The calculation method is the ratio of the surface area of ​​a sphere of the same volume as the object to the surface area of ​​the object. The sphericity of a sphere is equal to 1, and the sphericity of other objects is less than 1. In the present application, the sphericity of the particle size is determined by a dynamic image particle analysis system (Dandong Baite Instrument Co., Ltd.). In one embodiment of the present application, the sphericity of the granular material is 0.95-1, for example, the sphericity of the granular material can be 0.95, 0.951, 0.952, 0.953, 0.954, 0.955, 0.956, 0.957, 0.958, 0.959, 0.96, 0.97, 0.98, 0.99, 1.

[0061] In this application, "particle size" is also called "particle size" or "diameter". When a certain physical property or physical behavior of the measured particle is closest to a homogeneous sphere (or combination) of a certain diameter, the diameter (or combination) of the sphere is taken as the equivalent particle size (or particle size distribution) of the measured particle. Particle size is generally divided into a single particle size representing the size of a single particle and an average particle size representing a particle group composed of particles of different sizes. Since the shape of actual particles is usually non-spherical, it is difficult to directly express their size with a diameter. Therefore, in the field of particle size testing, for non-spherical particles, the particle size is usually characterized by an equivalent particle size (generally referred to as particle size). Equivalent particle size means that when a particle's physical property or physical behavior is closest to a homogeneous sphere (or combination) of a certain diameter, the diameter (or combination) of the sphere is taken as the equivalent particle size (or particle size distribution) of the measured particle. In this application, D50 refers to the particle size corresponding to when the volume cumulative particle size distribution percentage of a sample reaches 50%. Its physical meaning is that particles with a diameter larger than it account for 50%, and particles with a diameter smaller than it also account for 50%. D50 is also called the median diameter or median particle size. In this application, the particle size can be determined by Malvern particle size tester Mastersizer3000.

[0062] The particle size distribution of the granular material is determined by Malvern particle size tester Mastersizer 3000. In this article, the particle size distribution refers to the range consisting of the particle size of the smallest particle and the particle size of the largest particle measured by Mastersizer 3000.

[0063] In one embodiment of the present application, the particle size distribution of the granular material is 40-245 microns, for example, the particle size of the granular material can be 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 245 microns. Those skilled in the art should understand that at this time, the particle size of the smallest particle of the granular material is 40 microns, and the particle size of the largest particle is 245 microns.

[0064] In one embodiment of the present application, the particle size distribution of the granular material is 50-180 microns, for example, the particle size of the granular material is 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180 microns. In one embodiment of the present application, the particle size of the granular material conforms to the normal distribution pattern, the minimum particle size confirmed by detection is 50 microns, and the maximum particle size is 180 microns.

[0065] In one embodiment of the present application, in the process of forming the printing raw material, the granular material is mixed with the curing agent. The ratio of the curing agent to the granular material is (0.20-0.65):100 by mass. For example, the ratio of the curing agent to the granular material by mass can be: 0.20:100, 0.25:100, 0.30:100, 0.35:100, 0.40:100, 0.45:100, 0.50:100, 0.55:100, 0.60:100, 0.65:100.

[0066] In one embodiment of the present application, the curing agent is selected from one or more of sulfate esters, p-toluenesulfonic acid, xylenesulfonic acid, benzenesulfonic acid, sulfuric acid, phosphoric acid, mixed xylenesulfonic acid, lactic acid, citric acid, maleic anhydride, and oxalic acid. Preferably, the curing agent is a mixture of p-toluenesulfonic acid and sulfuric acid. In one embodiment of the present application, the ratio of p-toluenesulfonic acid to sulfuric acid is (65-70):(0.5-2.0) by mass.

[0067] In one embodiment of the present application, a sintering aid is added to the printing raw material. In one embodiment of the present application, the sintering aid is selected from one or more of amorphous silica, carbide, boride, oxide, spherical calcium aluminate, and aluminum fluoride granules, preferably amorphous silica, spherical calcium aluminate, and aluminum fluoride granules are used in combination. The amorphous silica can be prepared by a refining method of zirconium oxide material, or by a chemical reaction product of silica, silicon dioxide and other substances, and the amorphous silica can also be obtained by methods well known to those skilled in the art.

[0068] The D50 particle size of the amorphous silica is 0.5-3 μm, for example, the particle size of the amorphous silica can be 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2.0 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm, 3 μm. Preferably, the D50 particle size of the amorphous silica is 1 μm.

[0069] In the present application, the spherical calcium aluminate is prepared by mixing aluminum oxide and calcium oxide in a certain proportion, and the particle size of the spherical calcium aluminate is 55-150 μm. For example, the particle size of the spherical calcium aluminate can be 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 105 μm, 110 μm, 115 μm, 120 μm, 125 μm, 130 μm, 135 μm, 140 μm, 145 μm, 150 μm. Preferably, the D50 particle size of the spherical calcium aluminate is 150 μm.

[0070] The particle size of the aluminum fluoride granules is 60-185 μm. For example, the particle size of the aluminum fluoride granules can be 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 105 μm, 110 μm, 115 μm, 120 μm, 125 μm, 130 μm, 135 μm, 140 μm, 145 μm, 150 μm, 155 μm, 160 μm, 165 μm, 170 μm, 175 μm, 180 μm, 185 μm. Preferably, the D50 particle size of the aluminum fluoride granules is 185 μm.

[0071] In the present application, the preparation method of the spherical calcium aluminate is to mix aluminum oxide and calcium oxide in a certain proportion and then prepare it by electric melting.

[0072] The particle sizes of the spherical calcium aluminate, aluminum fluoride particles and amorphous silicon dioxide are determined by Malvern particle size tester Mastersizer 3000.

[0073] When amorphous silica, spherical calcium aluminate and aluminum fluoride particles are used as sintering aids, the ratio of the printing raw material to the sintering aid is 100:(1.2-10) by mass. Specifically, the ratio of the printing raw material to the sintering aid can be 100:1.2, 100:1.3, 100:1.4, 100:1.5, 100:1.6, 100:1.7, 100:1.8, 100:1.9, 100:2, 100:3, 100:4, 100:5, 100:6, 100:7, 100:8, 100:9, 100:10 by mass.

[0074] The ratio of the printing material to the amorphous silicon dioxide is 100:(0.2-2.2) by mass. Preferably, the ratio of the printing material to the amorphous silicon dioxide is 100:(0.3-1) by mass. Specifically, the ratio of the printing material to the sintering aid can be 100:0.3, 100:0.4, 100:0.5, 100:0.6, 100:0.7, 100:0.8, 100:0.9, 100:1 by mass.

[0075] The ratio of the printing material to the spherical calcium aluminate is 100:(0.2-0.8) by mass. Specifically, the ratio of the printing material to the spherical calcium aluminate is 100:(0.4-0.6) by mass. Further preferably, the ratio of the printing material to the spherical calcium aluminate is 100:0.5 by mass.

[0076] The ratio of the printing material to the aluminum fluoride granules is 100:(0.8-7) by mass. Preferably, the ratio of the printing material to the aluminum fluoride granules is 100:(1-6) by mass. Specifically, the ratio of the printing material to the aluminum fluoride granules is 100:1, 100:2, 100:3, 100:4, 100:5, 100:6 by mass.

[0077] In the present application, the role of the sintering aid is to further improve the powder spreading fluidity of the artificial granulated material, promote the sintering of the ceramic phase, and reduce the sintering temperature.

[0078] In one embodiment of the present application, the blank is prepared using a binder jet 3D printing technology. Specifically, a three-dimensional model of the blank to be printed is first established, and then the three-dimensional model is input into a computer. At this time, the number of layers of printing material required for the blank to be printed and the corresponding bonding areas between the layers, that is, the preset position for the binder injection, can be obtained in the computer. Specifically, the printing material is laid flat, and then the binder is sprayed to the preset position set by the computer, and the laying and binder injection processes are repeated; after printing is completed, the blank is cleaned of powder to obtain the blank that is the same as the three-dimensional model. Therefore, the role of the binder is to bond and fix the two adjacent layers of the printed material, thereby improving the bonding strength between the printing materials and improving the overall strength of the blank after printing.

[0079] The binder is selected from one or more of polyvinyl alcohol (PVA), polyvinyl ketone (PVP), polyacrylic acid (PAA), furan resin, phenolic resin, epoxy resin, urea-formaldehyde resin adhesive, polyvinyl acetal adhesive, polyvinyl acetate (PVAc) emulsion, acrylate water-based adhesive, polyurethane water-based adhesive, water glass, phosphate, and polyurethane acrylate, and the binder is preferably furan resin.

[0080] In one embodiment of the present application, after obtaining the blank, the blank is subjected to a strength test, and the tensile strength of the blank is 2.0-5.0 MPa. For example, the tensile strength of the blank may be 2.0 MPa, 2.1 MPa, 2.2 MPa, 2.3 MPa, 2.4 MPa, 2.5 MPa, 2.6 MPa, 2.7 MPa, 2.8 MPa, 2.9 MPa, 3.0 MPa, 3.1 MPa, 3.2 MPa, 3.3 MPa, 3.4 MPa, 3.5 MPa, 3.6 MPa, 3.7 MPa, 3.8 MPa, 3.9 MPa, 4.0 MPa, 4.1 MPa, 4.2 MPa, 4.3 MPa, 4.4 MPa, 4.5 MPa, 4.6 MPa, 4.7 MPa, 4.8 MPa, 4.9 MPa, or 5.0 MPa.

[0081] The tensile strength is measured by printing a sand mold eight-shaped test block for testing, wherein the measurement method and standard can refer to the industry standard: JB / T 7526-2008.

[0082] After printing, the blank needs to be cleaned before soaking. The cleaning method used in this application is compressed air blowing (the equipment model is oil-free air compressor JB1680-35). In this process, compressed air or air flow is used to blow the printed blank to clean the excess powder material. If the blank has low strength, its weak parts are easily damaged, so the blank needs to have high strength to ensure that the cleaning powder is not damaged.

[0083] In some embodiments of the present application, the powder cleaning process can also use manual powder cleaning, vibration powder cleaning, vacuum cleaner powder cleaning, or use a dedicated 3D printing powder cleaning device or powder cleaning machine.

[0084] There is a large porosity between the granular materials. The existence of this porosity leads to insufficient bulk density of the green body, which restricts the subsequent sintering of the ceramic and poses a high difficulty to the sintering process. In view of the problem of low density of ceramic green bodies in 3D printing process, it is an important means to improve the bulk density by post-processing process. Usually, a method of introducing fine powder into the gap is adopted. The process is to prepare the fine powder into a solution of a certain concentration, put the printed green body into the fine powder solution, and use normal pressure or pressurization to immerse the fine powder into the gap to increase the bulk density of the green body. In one embodiment of the present application, the green body also includes a post-processing step before sintering, and the post-processing step includes the following steps: soaking the green body in a fine powder solution to increase the bulk density of the green body.

[0085] The soaking time is 3 minutes to 60 minutes.

[0086] In one embodiment of the present application, the strength test of the blank is performed after the blank is printed and before the blank is soaked.

[0087] In this application, volume density refers to the mass of a material per unit volume (including the material entity and its open pores and closed pores) in its natural state, commonly known as bulk density. Volume density is an inherent property of any substance. That is, the value of volume density varies according to the type of material and its characteristics, but it does not actually affect the condition of the material. Therefore, the value of volume density is constant. Therefore, to calculate the volume density of an object, it can be calculated by dividing the mass of the object by the volume of the object. The volume density of the blank is 0.4% to 0.7%.

[0088] In one embodiment of the present application, the fine powder solution is a solution of a certain concentration of fine powder and a fine powder solvent, wherein the fine powder is selected from one or more of mullite, silicon carbide, silicon dioxide, aluminum oxide, zirconium oxide or silicon carbide; preferably mullite. The fine powder solvent is selected from one or more of water, methanol, ethanol, ethylene glycol, acetone, chloroform, carbon tetrachloride, ether, gasoline, benzene, toluene, and xylene; preferably methanol.

[0089] The concentration of the fine powder solvent is 30-70wt%, for example, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%. In one embodiment of the present application, during the sintering process, the green body is sintered for the first time at a temperature of T1, and after the first sintering, it is sintered for the second time at a temperature of T2, thereby obtaining the porous filter.

[0090] In one embodiment of the present application, during the first sintering process, the sintering temperature T1 is 800-900°C, the sintering time is 2h-4h, and during the first sintering process, the sintering pressure is normal pressure;

[0091] For example, during the first sintering process, the sintering temperature can be 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C, or 900°C; and the sintering time can be 2h, 2.5h, 3h, 3.5h, or 4h.

[0092] During the second sintering process, the sintering temperature T2 is 1200-1750° C., the sintering time is 4 h-6 h and / or during the second sintering process, the sintering pressure is normal pressure.

[0093] For example, during the second sintering process, the sintering temperature can be 1200℃, 1250℃, 1300℃, 1350℃, 1400℃, 1450℃, 1500℃, 1550℃, 1600℃, 1650℃, 1700℃, 1750℃; the sintering time can be 4h, 4.5h, 5h, 5.5h, 6h.

[0094] In the present application, after sintering is completed, the porous filter produced by sintering needs to be subjected to a mechanical strength test, wherein the compressive pressure of the porous filter at T3 temperature is 1.3MPa-2.5MPa, and the compressive pressure at T4 temperature is 0.6MPa-1.5MPa.

[0095] Preferably, the compressive strength of the porous filter at temperature T3 is 1.5 MPa-1.8 MPa, and the compressive strength at temperature T4 is 0.7 MPa-1.2 MPa.

[0096] The test method for compressive pressure is based on the compressive strength test method in GB / T 25319-2010 standard.

[0097] In one embodiment of the present application, the temperature range of T3 is 10-30°C, and the temperature range of T4 is 900-1200°C.

[0098] For example, the T3 temperature may be 10, 15, 20, 25, 30° C. For example, the T4 temperature may be 900, 950, 1000, 1050, 1100, 1150, 1200° C.

[0099] The present application also provides a porous filter, characterized in that it is prepared using any of the methods described above.

[0100] Example

[0101] The present application provides a general and / or specific description of the materials and test methods used in the experiments. In the following examples, unless otherwise specified, % represents wt%, i.e., mass percentage. The reagents or instruments used without indicating the manufacturer are all conventional reagent products that can be obtained commercially.

[0102] Example 1

[0103] Example 1-1

[0104] Step 1, silica, alumina, phenolic resin, ethanol, methanol and polyethylene glycol are mixed in a mass ratio of 40:60:1:1:9:0.5, and then granulated by a spray granulation method to prepare granules with a sphericity of 0.95-1 and a particle size range of 40-245 microns.

[0105] The sphericity test method is determined by dynamic image particle analysis system (Dandong Better Instrument Co., Ltd.) in accordance with GB / T 39251-2020.

[0106] The particle size test method was determined by Malvern Mastersizer 3000.

[0107] Step 2, mixing the granular material and the curing agent (the curing agent is a mixture of p-toluenesulfonic acid and sulfuric acid, and the mass ratio of p-toluenesulfonic acid to sulfuric acid is 68:1.5) at a mass ratio of 100:0.3 to form a printing material.

[0108] Step 3, establish a three-dimensional model of the sample to be printed, then input the three-dimensional model into a computer, add a sintering aid (mixed with amorphous silica, spherical calcium aluminate, and aluminum fluoride particles) to the printing raw material, and lay it flat, and spray a binder at a preset position, and repeat the laying and spraying process to obtain a green body;

[0109] The binder is furan resin, the particle size D50 of the amorphous silicon dioxide used is 1 μm, the particle size of the spherical calcium aluminate used is 150 μm, and the particle size of the aluminum fluoride particles used is 185 μm;

[0110] Amorphous silicon dioxide, spherical calcium aluminate and aluminum fluoride particles are mixed in a mass ratio of 0.3:0.5:1.

[0111] Step 4, after obtaining the green body, perform strength test on the green body, record the data of tensile strength, and statistically enter it into Table 1.

[0112] The tensile strength is measured by printing sand casting blocks and testing them according to JB / T7526-2008.

[0113] Step 5: soak the obtained printed body in a mullite powder solution with a mass concentration of 50 wt % for 60 min.

[0114] Step 6, sintering the densified green body for the first time, the temperature of the first sintering is 800°C, the time is 2h, and the pressure is normal pressure.

[0115] Then, a second sintering was carried out under the condition of introducing air. The temperature of the second sintering was 1450°C, the time was 4 hours, and the pressure was normal pressure.

[0116] Step 7: After sintering, the obtained ceramic product needs to be tested for mechanical strength. The test method refers to the compressive strength test method in GB / T25319-2010 standard. The results are summarized in Table 2. The temperature T3 is room temperature and the temperature T4 is 1000 degrees Celsius.

[0117] Step 8: Perform high temperature casting test to characterize the obtained ceramic filter product

[0118] According to the above 7 steps, a spherical ceramic filter with a diameter of 100 mm and a thickness of 22 mm was prepared, the spherical filter was placed in a suitable metal runner, the gray iron was melted to a temperature of 1500±20℃, a casting test bench was built, and the gray iron liquid was transported to the casting table with a ladle; the direct casting method was used to allow the molten iron to pass directly through the filter, and the application performance of the filter was characterized by statistically analyzing the cast iron liquid quality and casting time.

[0119] Cast iron quality test method: In the direct casting method, tilt the ladle at a certain angle to ensure that the molten iron passes through the filter at a uniform speed during the casting process, and monitor the filter in real time. When the filter is damaged, stop casting, and count the quality of the cast iron, and record it as the highest casting amount. The results are counted in Table 3.

[0120] Casting time test method: Take another filter prepared according to the above 7 steps and use 300kg of molten iron. In the direct casting method, tilt the ladle at the same angle as in the casting time test method to ensure that the molten iron passes through the filter at the same or similar speed as in the casting time test method during the casting process. Count the time required for the molten iron to pass through the filter, and enter the results into Table 4.

[0121] Example 1-2

[0122] The same operation as Example 1-1 was performed, except that the mass ratio of silicon dioxide to aluminum oxide in step 1 was changed to 45:55. The results are summarized in Tables 1, 2, 3, and 4.

[0123] Examples 1-3

[0124] The same operation as Example 1-1 was performed, except that the mass ratio of silicon dioxide to aluminum oxide in step 1 was changed to 50:50. The results are summarized in Tables 1, 2, 3, and 4.

[0125] Examples 1-4

[0126] The same operation as Example 1-1 was performed, except that the mass ratio of silicon dioxide to aluminum oxide in step 1 was changed to 55:45. The results are summarized in Tables 1, 2, 3, and 4.

[0127] Examples 1-5

[0128] The same operation as Example 1-1 was performed, except that the mass ratio of silicon dioxide to aluminum oxide in step 1 was changed to 60:40. The results are summarized in Tables 1, 2, 3 and 4.

[0129] Examples 1-6

[0130] The same operation as Example 1-1 was performed, except that the mass ratio of silicon dioxide to aluminum oxide in step 1 was changed to 30:70. The results are summarized in Tables 1, 2, 3, and 4.

[0131] Examples 1-7

[0132] The same operation as Example 1-1 was performed, except that the mass ratio of silicon dioxide to aluminum oxide in step 1 was changed to 70:30. The results are summarized in Tables 1, 2, 3, and 4.

[0133] Examples 1-8

[0134] The same operation as Example 1-1 was performed, except that the silica and alumina in step 1 were replaced with only silica. The results were statistically summarized in Tables 1, 2, 3, and 4.

[0135] Examples 1-9

[0136] The same operation as Example 1-1 was performed, except that the silicon dioxide and aluminum oxide in step 1 were replaced with aluminum oxide only. The results were summarized in Tables 1, 2, 3, and 4.

[0137] Examples 1-10

[0138] The same operation as Example 1-1 was performed, except that the silicon dioxide and aluminum oxide in step 1 were replaced with only silicon carbide. The results were summarized in Tables 1, 2, 3, and 4.

[0139] Embodiment 1-11

[0140] The same operation as Example 1-1 was performed, except that the ratio of silica, alumina and phenolic resin in step 1 was changed to 40:60:3. The results are summarized in Tables 1, 2, 3 and 4.

[0141] Examples 1-12

[0142] The same operation as Example 1-1 was performed, except that the ratio of silica, alumina and phenolic resin in step 1 was changed to 40:60:5. The results are summarized in Tables 1, 2, 3 and 4.

[0143] Examples 1-13

[0144] The same operation as in Example 1-3 was performed, except that the binder in step 3 was changed from furan resin to phenolic resin. The results are summarized in Table 1, Table 2, Table 3, and Table 4.

[0145] Examples 1-14

[0146] The same operation as in Example 1-3 was performed, except that the binder in step 3 was changed from furan resin to polyvinyl alcohol. The results are summarized in Table 1, Table 2, Table 3, and Table 4.

[0147] Examples 1-15

[0148] The same operation as in Example 1-3 was performed, except that the binder in step 3 was changed from furan resin to silicate powder. The results are summarized in Table 1, Table 2, Table 3, and Table 4.

[0149] Examples 1-16

[0150] The same operation as in Example 1-3 was performed, except that the mass ratio of amorphous silica, spherical calcium aluminate, and aluminum fluoride particles in step 3 was changed. The results are summarized in Tables 1, 2, 3, and 4.

[0151] Examples 1-17

[0152] The same operation as in Example 1-3 was performed, except that the mass ratio of amorphous silica, spherical calcium aluminate, and aluminum fluoride particles in step 3 was changed. The results are summarized in Tables 1, 2, 3, and 4.

[0153] Examples 1-18

[0154] The same operation as in Example 1-3 was performed, except that the mass ratio of amorphous silica, spherical calcium aluminate, and aluminum fluoride particles in step 3 was changed. The results are summarized in Tables 1, 2, 3, and 4.

[0155] Examples 1-19

[0156] The same operation as in Example 1-3 was performed, except that the mass ratio of amorphous silica, spherical calcium aluminate, and aluminum fluoride particles in step 3 was changed. The results are summarized in Tables 1, 2, 3, and 4.

[0157] Examples 1-20

[0158] The same operation as in Example 1-3 was performed, except that the mass ratio of amorphous silica, spherical calcium aluminate, and aluminum fluoride particles in step 3 was changed. The results are summarized in Tables 1, 2, 3, and 4.

[0159] Embodiment 1-21

[0160] The same operation as in Example 1-3 was performed, except that the mass ratio of amorphous silica, spherical calcium aluminate, and aluminum fluoride particles in step 3 was changed. The results are summarized in Tables 1, 2, 3, and 4.

[0161] Examples 1-22

[0162] The same operation as in Example 1-3 was performed, except that the mass ratio of amorphous silica, spherical calcium aluminate, and aluminum fluoride particles in step 3 was changed. The results are summarized in Tables 1, 2, 3, and 4.

[0163] Examples 1-23

[0164] The same operation as in Example 1-3 was performed, except that no sintering aid was added. The results are summarized in Table 1, Table 2, Table 3, and Table 4.

[0165] Examples 1-24

[0166] The same operation as in Example 1-3 was performed, except that the first sintering temperature was changed to 900° C. The results are summarized in Table 1, Table 2, Table 3, and Table 4.

[0167] Examples 1-25

[0168] The same operation as in Example 1-3 was performed, except that the first sintering temperature was changed to 700° C. The results are summarized in Table 1, Table 2, Table 3, and Table 4.

[0169] Examples 1-26

[0170] The same operation as in Example 1-3 was performed, except that the first sintering temperature was changed to 1100° C. The results are summarized in Table 1, Table 2, Table 3, and Table 4.

[0171] Comparative Example 1-1

[0172] The same operation as Example 1-1 was performed, except that the ratio of silica, alumina and phenolic resin in step 1 was changed to 40:60:0.5. The results are summarized in Tables 1, 2, 3 and 4.

[0173] Comparative Examples 1-2,

[0174] The same operation as in Example 1-1 was performed, except that no phenolic resin was added during the granulation process in step 1. The results are summarized in Tables 1, 2, 3, and 4.

[0175] Comparative Examples 1-3

[0176] The same operation as Example 1-1 is performed, except that steps 1 to 6 are omitted, and in step 8, the ceramic filter prepared in Example 1-1 is replaced with a traditional foam silicon carbide filter CF-2BA produced by Shengquan. The results are summarized in Tables 1, 2, 3, and 4.

[0177] Comparative Examples 1-4

[0178] The same operation as Example 1-1 is performed, except that steps 1 to 6 are omitted, and in step 8, the ceramic filter prepared in Example 1-1 is replaced with an alumina filter FCF-3 produced by Shengquan. The results are summarized in Tables 1, 2, 3, and 4.

[0179] Table 1 Performance parameters of printing eight-character blocks

[0180]

[0181]

[0182] Note: Comparative Examples 1-3 and 1-4 are finished filters, which were only characterized by compressive pressure test and high-temperature casting test, so the composition and tensile strength data are not statistically analyzed.

[0183] In the present application, in Table 1, it can be seen from Examples 1-3 and 1-13 to 1-15 that the choice of binder will significantly affect the tensile strength after printing into a blank, and the increase in the amount of amorphous silica and aluminum fluoride granules added will slightly reduce the tensile strength. When the fine refractory granules are composed of silica and alumina, their tensile strength is generally higher than that of a single component (Examples 1-1 to 1-10). At the same time, when the binder is too low, the tensile strength will be lower (Comparative Example 1-1). As in Examples 1-1 to 1-8, Examples 1-11 to 1-12, and Examples 1-16 to 1-22, the blank tensile strength in these embodiments is greater than 2MPa, which illustrates that the preparation method of the porous filter disclosed in the present application can well meet the requirements of the powder cleaning method, and will not cause powder blowing rupture due to too low strength.

[0184] Table 2 Performance parameters of ceramic filter after sintering

[0185]

[0186]

[0187]

[0188] Note: Comparative Examples 1-3 and 1-4 are finished filters, which were only characterized by compressive stress test and high-temperature casting test, so the sintering temperature data are not counted.

[0189] After the filter is sintered, it is required to have a certain strength at room temperature. Technical personnel in this field believe that when the compressive pressure at room temperature is above 1.38Mpa, the filter is not easily damaged during operation and transportation, thereby avoiding the situation where the filter cannot be used due to physical damage. At the same time, under high temperature conditions, it is also necessary to ensure that the compressive pressure is greater than 0.65MPa, so that it can withstand the impact force of molten iron casting at high temperature to damage the filter skeleton and ensure its performance under high temperature conditions.

[0190] As the content of silica added increases, the tensile strength in Table 1 and the compressive pressure at room temperature in Table 2 both increase. Although it can be seen from Examples 1-8 in Table 1 that the tensile strength can reach 2.80 MPa when there are only silica and phenolic resin, alumina is more stable than silica at high temperatures. Therefore, it can be seen from Table 2 that excessive addition of silica will cause a sudden drop in the compressive pressure of the filter at high temperatures (such as Examples 1-7 to 1-9).

[0191] It can be seen from Examples 1-6 and 1-7 that with the increase in the amount of phenolic resin added, the physical properties of the filter in Tables 1 and 2 both increase first and then decrease, which indicates that too much phenolic resin has a negative effect on transformer performance.

[0192] At the sintering temperature of the present application, aluminum fluoride, as a sintering aid, will become a liquid phase at a certain temperature. The liquid phase components will promote the dense sintering of ceramics and eliminate bubbles between particles. When the amount of aluminum fluoride is too much, it will have a negative effect on the sintering of ceramics. When the amount of aluminum fluoride is too little, the sintering power is insufficient and it is difficult to promote the dense sintering of ceramics.

[0193] Comparative Examples 3 and 4 are prior art. The compressive stress at temperatures T3 and T4 can barely meet the requirements or cannot quite meet the requirements. The effects of Examples 1-1 to 1-5, 1-11 to 1-12, and 1-16 to 1-21 are all better than the prior art.

[0194] Table 3 Characterization performance of ceramic filter high temperature casting test (maximum casting amount)

[0195]

[0196]

[0197] Note: 1. In Table 3, the blank area represents the statistical stage of the results in Tables 1 and 2. This embodiment cannot be printed into a green body or cannot be sintered, so the high-temperature casting test in step 8 cannot be performed. Therefore, there is no data in the blank area;

[0198] 2.Other data are rounded to the nearest integer.

[0199] Table 4 Characterization performance of ceramic filter high temperature casting test (casting time)

[0200] Casting time(s) Example 2-1 69 Example 2-2 66.8 Example 2-3 65 Embodiment 2-4 63.2 Embodiment 2-5 61.2 Embodiment 2-6 79 Embodiment 2-7 76 Embodiment 2-8 Broken during pouring Embodiment 2-9 Broken during pouring Embodiment 2-10 Broken during pouring Example 2-11 64 Example 2-12 73 Example 2-13 -- Embodiment 2-14 -- Example 2-15 -- Example 2-16 63 Example 2-17 65 Example 2-18 68 Example 2-19 67 Example 2-20 68 Example 2-21 71 Example 2-22 -- Example 2-23 Broken during pouring Example 2-24 Broken during pouring Example 2-25 Broken during pouring Comparative Example 2-1 Broken during pouring Comparative Example 2-2 -- Comparative Examples 2-3 84 Comparative Examples 2-4 80

[0201] Note: 1. In Table 4, the blank area represents the statistical stage of the results in Tables 1 and 2. This embodiment cannot be printed into a green body or cannot be sintered, so the high-temperature casting test in step 8 cannot be performed. Therefore, there is no data in the blank area;

[0202] 2. Midway casting failure means that during the casting of 300 kg of molten iron, the filter is damaged, and the casting is stopped at this time. The casting time of this embodiment is not counted and is deemed to have failed the casting time test.

[0203] 3. Other casting times shall be rounded to the nearest integer.

[0204] It should be understood that once the filter is sintered, the width, shape, and length of its internal channel are immediately finalized. During the sintering process, there is a certain temperature difference between the internal temperature and the surface temperature of the filter. Therefore, even if the internal structure is finalized, it may not be sintered completely or residues may block the filter channel. In the actual production process, this will cause the metal liquid to stay in or pass through the filter for a longer time, prolonging the casting time. Even the high-temperature metal liquid will destroy the internal structure of the filter, causing it to lose its proper filtering effect. Therefore, the casting time should be as short as possible. Similarly, in actual production, the filter needs to pass as much metal liquid as possible, that is, to ensure the highest possible maximum casting volume to ensure the service life of the filter.

[0205] Therefore, the formula of the filter preparation material will directly affect the quality of the filter after sintering (whether the filter channel is complete, whether the channel is blocked, whether there are fragments and debris generated after sintering inside the filter, etc.), and then affect the casting time and maximum casting amount.

[0206] In Table 3, when the content of alumina added is 60% (Example 2-1), the maximum casting amount is the best, which is 752kg. When the content of alumina added is 70% (Example 2-6), the maximum casting amount is reduced to 483, but it is still better than the maximum casting amount of the prior art (Comparative Example 2-3 and Comparative Example 2-4). Among them, Examples 2-1 to 2-5, Example 2-11, Example 2-12, Example 2-16 to Example 2-21 all show better performance than other examples. The maximum casting amount is about 1.5 to 2 times that of the prior art, indicating that the filter prepared by the preparation method provided in Examples 1-1 to 1-5, Example 1-11, Example 1-12, Example 1-16 to Example 1-21 has very good thermal stability, and its performance can fully meet the production needs.

[0207] In Table 4, the data in Table 3 are combined. In Table 3, the casting amount that does not exceed 300kg will not pass the casting time test, so such filters will be damaged during the casting process, and are therefore counted as "broken during casting" in Table 4. Examples 2-6 and 2-7, which perform well in Table 3, have shorter casting times than the prior art. It is speculated that the filters made by the preparation methods provided in Examples 1-6 and 1-7 may have residues blocking the filtration channels, indicating that the filters prepared by Examples 1-6 and 1-7 are not as strong as those prepared by Examples 1-1 to 1-5, 1-11, and 1-12, and the filters prepared by Examples 1-16 to 1-21. This also explains the phenomenon that the highest casting amount in Table 3 does not exceed 500kg, but its performance is still slightly better than the prior art. The performance of Examples 2-1 to 2-5, 2-11, 2-12, and 2-16 to 2-21 is still excellent, generally between 60 and 70 seconds, which greatly shortens the casting time compared with the prior art.

[0208] In summary, the filter prepared by the preparation method provided by the present application can have a tensile strength of more than 2MPa in the green body stage, which is sufficient to overcome the pressure brought by the powder cleaning machine during the powder cleaning process. After sintering, although the silicon dioxide and aluminum oxide in the composition will affect the compressive pressure at room temperature and high temperature respectively, both can fully meet the production needs, and there will be no situation where one performance is too high and the other performance is too low, which will cause the ceramic filter to be damaged during use. And, the filter prepared according to the method of the present application has a maximum casting amount of more than 750kg, which is 1.5-2 times that of the prior art in general. At the same time, the casting time is significantly improved compared with the prior art, which improves the filtration efficiency and production efficiency of the filter. This shows that the filter prepared by the preparation method provided by the present application has excellent performance in all aspects, has high strength, high thermal stability, and has a faster casting time and higher casting amount compared with the prior art. Therefore, the possibility of the filter being thin, fragile, slag falling and damaged is greatly reduced, which can well meet the work needs of daily transportation and high-temperature filtration.

[0209] The above is only the preferred embodiment of the present application, and does not limit the present application in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present application without departing from the technical solution of the present application still falls within the protection scope of the technical solution of the present application.

Claims

1. A method for preparing a porous filter, wherein: The method comprises: Granulation: fine refractory particles, binder, solvent and additives are mixed in a mass ratio of (90-100): (1-5): (5-15): (0.5-10), and then granulated to prepare granular materials; Printing materials: Mix the granular material and the curing agent to form printing materials; Establishing a three-dimensional model of the blank to be printed, and then inputting the three-dimensional model into a computer to obtain the number of layers of printing material required for the blank to be printed and the corresponding bonding areas between the layers, that is, the preset positions for the injection of the binder; Laying the printing material flat, spraying a binder at a preset position, and repeating the laying and spraying binder processes to obtain a blank; The green body is sintered to form a porous filter.

2. The method according to claim 1, wherein the fine refractory particles are selected from one or more of mullite, silicon carbide, silicon dioxide, alumina, and zirconium oxide; preferably silicon dioxide and alumina, and more preferably, the ratio of silicon dioxide to alumina is 1:(0.6-1.5) by mass; and / or The adhesive is selected from one or more of furan resin, phenolic resin, urea-formaldehyde resin adhesive, polyvinyl acetal adhesive, polyvinyl acetate (PVAc) emulsion, acrylic acid ester water-based adhesive, rubber emulsion adhesive, polyurethane water-based adhesive, cement, gypsum, water glass, lime, and clay; and / or The solvent is selected from one or more of water, methanol, ethanol, ethylene glycol, acetone, chloroform, carbon tetrachloride, ether, gasoline, benzene, toluene and xylene; the solvent is preferably water or methanol; and / or The additive is selected from one or more of sulfates, sulfonates, phosphates, amine salts, and polyethylene glycol.

3. The method according to claim 2, wherein: The ratio of the fine refractory particles to the binder is 100:(1-3) by mass; and / or The sphericity of the granules is 0.95-1.

4. The method according to claim 1, wherein: The particle size distribution of the granules is 40-245 microns.

5. The method according to claim 1, wherein: In the process of forming the printing raw material, the mass ratio of the curing agent to the granular material is (0.20-0.65):

100.

6. The method according to claim 5, wherein: The curing agent is selected from one or more of sulfate, p-toluenesulfonic acid, xylenesulfonic acid, benzenesulfonic acid, sulfuric acid, phosphoric acid, mixed xylenesulfonic acid, lactic acid, citric acid, maleic anhydride and oxalic acid.

7. The method according to claim 1, wherein: Before tiling, a sintering aid is added to the printing raw material, and the mass ratio of the printing raw material to the sintering aid is 100:(1.2-10).

8. The method according to claim 7, wherein: The sintering aid is selected from one or more of amorphous silica, carbide, boride, oxide, spherical calcium aluminate, and aluminum fluoride particles, preferably amorphous silica, spherical calcium aluminate, and aluminum fluoride particles are used in combination.

9. The method according to claim 8, wherein: The D50 particle size of the amorphous silicon dioxide is 0.5-3 μm.

10. The method according to claim 1, wherein: The binder is selected from one or more of polyvinyl alcohol (PVA), polyvinyl ketone (PVP), polyacrylic acid (PAA), furan resin, phenolic resin, epoxy resin, urea-formaldehyde resin adhesive, polyvinyl acetal adhesive, polyvinyl acetate (PVAc) emulsion, acrylate water-based adhesive, polyurethane water-based adhesive, water glass, phosphate, and polyurethane acrylate, and the binder is preferably furan resin.

Citation Information

Patent Citations

  • Three-dimensional printing molding preparation method for porous ceramic for filtration

    CN107098717A

  • Method for preparing high-performance structural ceramic based on binder spraying technology

    CN117303877A

  • 3DP manufacturing method of aluminum oxide ceramic part

    CN117447190A

  • Preparation method of high-density and high-strength 3D printing silicon carbide ceramic

    CN118026690A

  • Ceramic particles prepared based on thermocuring process and used for binder jet printing, granulation method and application

    CN118754627A